ANALISIS KUALITAS PRODUK, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN KOPI NOESA WILAYAH KOTA SURABAYA - ARISTA, OCI (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the effect of the quality of goods, the quality of administration and costs on the fulfillment of Surabaya Noesa Coffee shoppers. This exploration is a research study with a collaborative plan. The research population is all consumers of Noesa Coffee Surabaya. This exploratory trial adds up to 170 subscribers. The information acquisition strategy uses surveys that have been tested for validity and unwavering quality. The procedure for checking information in this exploration is different from relapse. The results of this exploration show that product quality, service quality, and price perception have a positive and massive impact on the fulfillment of Surabaya Noesa Coffee buyers.